Wet-grassland breeding bird conservation in Germany: current status and future perspectives - Maasri, Alain; Barkow, Andreas; Ludwig, Jürgen; Belting, Heinrich (Frontiers in Conservation Science, 2023)
The decline of wet-grassland breeding bird populations across Europe, and Germany more specifically, continues unabated. In an effort to address this ongoing issue, we conducted a Horizon Scanning survey to identify the current strengths, weaknesses, future opportunities, and threats for wet-grassland breeding bird conservation across both continental and Atlantic biogeographic regions in Germany. We conducted the survey in 2022 and targeted primarily the community of conservation practitioners. We structured the survey with nine simple questions to identify the profile of the participants and collect their expert opinions. Our results confirm established challenges for bird conservation and bring into the spotlight emerging opportunities and threats. Thus, we summarize here the results of this survey and provide recommendations to decision-makers and stakeholders to work collectively towards the recovery of wet-grassland breeding bird populations in Germany and preserve grassland biodiversity for future generations.